Correlation of Beta-2 Adrenergic Receptor Expression in Tumor-Free Surgical Margin and at the Invasive Front of Oral Squamous Cell Carcinoma - Lauris, José Roberto Pereira; Kowalski, Luiz Paulo; Nonogaki, Suely; García-García, Abel; Pérez-Sayáns, Mario; Suárez-Peñaranda, José-Manuel; Assao, Agnes; Lauand, Gustavo Amaral; Bravo-Calderón, Diego Maurício; Oliveira, Denise Tostes; Marana, Aparecido Nilceu (Journal of Oncology, 2016)
Background. The beta-2 adrenergic receptor is expressed by neoplastic cells and is correlated with a wide spectrum of tumor cell mechanisms including proliferation, apoptosis, angiogenesis, migration, and metastasis. Objectives. The present study aimed to analyze the expression of the beta-2 adrenergic receptor (β2-AR) in tumor-free surgical margins of oral squamous cell carcinomas (OSCC) and at the invasive front. Sixty-two patients diagnosed with OSCC, confirmed by biopsy, were selected for the study. The clinicopathological data and clinical follow-up were obtained from medical records and their association with β2-AR expression was verified by the chi-square test or Fischer’s exact test. To verify the correlation of β2-AR expression in tumor-free surgical margins and at the invasive front of OSCCs, Pearson’s correlation coefficient test was applied. Results. The expression of β2-AR presented a statistically significant correlation between the tumor-free surgical margins and the invasive front of OSCC (r=0.383; p=0.002). The immunohistochemical distribution of β2-AR at the invasive front of OSCC was also statistically significant associated with alcohol (p=0.038), simultaneous alcohol and tobacco consumption (p=0.010), and T stage (p=0.014). Conclusions. The correlation of β2-AR expression in OSCC and tumor-free surgical margins suggests a role of this receptor in tumor progression and its expression in normal oral epithelium seems to be constitutive.